A high-quality chromosome-level genome assembly of Ficus hirta - Huang, Weicheng; Ding, Yamei; Fan, Songle; Liu, Wanzhen; Chen, Hongfeng; Segar, Simon; Compton, Stephen G.; Yu, Hui (Scientific data, 2024)
Ficus species (Moraceae) play pivotal roles in tropical and subtropical ecosystems. Thriving across diverse habitats, from rainforests to deserts, they harbor a multitude of mutualistic and antagonistic interactions with insects, nematodes, and pathogens. Despite their ecological significance, knowledge about the genomic background of Ficus remains limited. In this study, we report a chromosome-level reference genome of F. hirta , with a total size of 297.27 Mb, containing 28,625 protein-coding genes and 44.67% repeat sequences. These findings illuminate the genetic basis of Ficus responses to environmental challenges, offering valuable genomic resources for understanding genome size, adaptive evolution, and co-evolution with natural enemies and mutualists within the genus.